PERBAIKAN DESAIN DINDING PENAHAN TANAH URUG PADA SPBU DI JALAN SILIWANGI BANTEN - Sentosa, Gregorius Sandjaja; Prihatiningsih, Aniek; Putra, Ricky; Bachtiar, William Pratama (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
A site of land used as gas station has been filled to the ground level with the level of the road that passes near the station site. To hold the landfill, a 4000mm high retaining wall was built, but the construction of this wall was made without adequate planning resulting in damage in the form of collapse in several parts of the wall. The andesite stone material used is a textured stone that tends to be round with a smooth surface and is bound with a cement mortar that is too thick so that the bond is not strong enough. The damage of the wall has been identified and could lead to the collapse of the wall which could endanger people who pass near the wall. The proposed improvement is to partially dismantle the old wall and construct a new retaining wall built on the inside of the land along the old wall where the old retaining wall was dismantled. To ensure that the new wall has a strong bond with the old wall, at some point bonding reinforcement are installed between the old and new walls. The new wall is designed with sufficient attention to overturning, shearing, the bearing capacity of soil and overall stability, according to standard design. The andesite stone material used is crushed so that the surface texture of the stone is not slippery to ensure a better bond with the sand-cement mixture. The composition of the cement-sand mortar is made 1:4. To prevent groundwater from being trapped behind the wall, groundwater drainage channels have been designed at several points so that water that seeps into the soil layer can immediately spill out through these channels. This design recommendation was provided to the landowners and subsequently construction of additional strengthening wall has been carried out. In designing and analyzing this additional wall.